2020
DOI: 10.1038/s41529-020-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Can a simple topological-constraints-based model predict the initial dissolution rate of borosilicate and aluminosilicate glasses?

Abstract: Tuning glass composition to obtain targeted properties generally relies on empirical approaches. However, a deep understanding of the physical and chemical mechanisms linking glass composition to its structure and properties would enable developing reliable predictive models. Indeed, although empirical models are usually able to interpolate composition-property relationships within a given compositional envelope, they often fail at extrapolating predictions far from their training domain. Here, as an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 42 publications
3
60
0
Order By: Relevance
“…A group of 20 borosilicate and aluminosilicate glasses with compositions listed in Table 1 have been studied. Glass sample preparation and characterization details were reported in our previous paper 18 . A brief introduction is presented here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A group of 20 borosilicate and aluminosilicate glasses with compositions listed in Table 1 have been studied. Glass sample preparation and characterization details were reported in our previous paper 18 . A brief introduction is presented here.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al 16 proposed a topology‐informed ML approach, which can overcome the limitations (e.g., unreliable extrapolations and violation of the laws of physics) of traditional ML, offering a promising route to predict the properties of materials in a robust way. By using the topological constraint theory (TCT), we have demonstrated that simple topological constraints enumeration based on glass composition can be used to correlate the initial dissolution rate ( r 0 ) and, based on which, it was able to predict the dissolution rate of a series of aluminosilicate and borosilicate glasses 18 . It was found that a few aluminosilicate glasses were outliers in the correlation analysis with TCT due to preferential dissolution; nevertheless, when using corrected glass compositions accounting for the fast leaching of alkali ions, the TCT model provided reasonable predictions of r 0 values for aluminosilicate glasses with high alkali content glasses after modifying the compositions 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the angular BB constraints associated with four-fold Al atoms have been suggested by many studies to be notably weaker than those associated with Si atoms. 27,28,[69][70][71][72] This has been attributed to the fact that the nearby presence of a charge-compensating cation tends to destabilize the angular environment of four-fold coordinated Al atoms. 28 Second, ionic Ca-FO constraints are expected to exhibit a low bond energy and, hence, to break at low temperature.…”
Section: Regime Conditionmentioning
confidence: 99%
“…This ranking is based on the following observations. First, the angular BB constraints associated with four‐fold Al atoms have been suggested by many studies to be notably weaker than those associated with Si atoms 27,28,69–72 . This has been attributed to the fact that the nearby presence of a charge‐compensating cation tends to destabilize the angular environment of four‐fold coordinated Al atoms 28 .…”
Section: Rigidity Diagram Of the Cas Ternary Systemmentioning
confidence: 99%